Interrupted lines: women humorists in the humor press (Argentina, 1974-1984) (Tempo e Argumento, 2020)
In Argentina, graphic humor was a mostly male profession until the eighties of the twentieth century when several women - Maitena, Patricia Breccia, Maria del Carmen Alcobre, Petisuí, Ana von Reuber˗ began publishing their strips in the magazines of Ediciones de la Urraca. Before this irruption, between 1974 and 1984, Nelly Hoijman, Patricia Breccia, Lucía Capozzo and Marta Vicente produced and published humorous strips in those graphic humor magazines where male firms prevailed. For various reasons and except Breccia, the rest did it for a short period and then dedicated to other professions. Theoretically and methodologically inspired by the contributions of social history aimed at problematizing the invisibility of women in social life. Moreover, in the questions and studies that feminists art historian such as Linda Nochlin and Griselda Pollock have been carrying out for decades in relation to the place of women in the "fine arts", and Whitney Chadwick and Isabelle de Courtivron on the relationship between creativity and intimate relationships, in this work we analyze the passage of these women through humor graphic. This article focus in identifying the social conditions of their production as well as analyzing the themes and representations embodied in their respective works in light of the other contents of the magazines where they published. Its aim is to generate a contribution to a new history of graphic humor that accounts for the place of women in humorous production and in the mass media.Keywords: Woman Artist. Humor. Periodical Press. Argentine.